Penerapan Fermentasi Pakan Ternak dan Pemasaran Online untuk Meningkatkan Pendapatan Petani - Muchamad Zaenuri; Suswanta Suswanta; Muhammad Iqbal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Dukuh Sikepan Ngagrong Village is one of the villages located in Gladagsari District, Boyolali Regency, Central Java Province. Plantations and animal husbandry are the sources of livelihood for the people of Dukuh Sikepan, most of whom work as farmers and breeders. Also, the limited knowledge of residents about animal feed fermentation has made residents only provide feed with ordinary grass, which is only found in the rainy season. So that during the dry season, residents have to buy feed elsewhere at a higher cost. The not yet optimal marketing of agricultural products and development is also an obstacle for Sikepan residents. Thus, it is necessary to have a community service program that is expected to help the people of Sikepan Hamlet reduce the problems they are facing. Through the method of extension, education, and assistance to develop public knowledge to recognize and utilize agricultural knowledge about animal feed fermentation and education about post-harvest online marketing in Sikepan Hamlet, it is necessary to do it. KKN students, assisted by Field Supervisory Lecturers, carry out community service programs that interact with the community. The KKN-PPM program is beneficial for residents in carrying out livestock feed fermentation, providing technical training to enable farmers to do what they need. Besides that, with online marketing training, mothers and adolescents can sell their products smartly.